Cross-media, co-creative and current: New strategies for educating talent for Danish children's film and television in the 2020s. Issue 2 (23rd November 2021) - Redvall, Eva Novrup
Abstract : page_184 other This article analyses recent developments in Danish film and television education through a case study of a new training initiative for creating content for children and young audiences. Following an outline of traditional training and career trajectories in the Danish screen industries in general, and for working with children's film and television specifically, the case study investigates the guiding ideas behind Manuskriptskolen for børnefiktion ('The Cross-Media School of Children's Fiction'), which was established in 2020. The school marks a new approach to Danish film education in several ways. First, by creating a training ground focusing on a specific audience, rather than on screenwriting or film-making more generally. Second, by thinking of content for this audience as fundamentally multi-platform and teaching students storytelling across different media from the outset. Third, by insisting that creating content for this audience calls for having knowledge about the current lives of young people and their media use, and encouraging strategies for engaging or even co-creating content with them. The article builds on qualitative interviews, document analysis and observations at industry events as part of the research project Reaching Young Audiences: Serial Fiction and Cross-Media Storyworlds for Children and Young Audiences.